ANALISIS KONTRASTIF PEMARKAH LOKATIF ‘DI’ DALAM BAHASA INDONESIA DAN IN, ON, AT DALAM BAHASA INGGRIS - Kusumaningrat, Cokorda Istri Mas (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 22 (2015): March 2015, 2016)
In second language learning, understanding the mother tongue is as important as understanding the second language for the learners. Contrastive analysis provides a means to compare and find similarities and differences between the two languages so that the exchange of meaning can be done with accuracy. The word ‘di’ and at have the same function as a locative marker, however, each has distinct uses in the sentence. Locative marker 'di' in Bahasa is used to express a place while locative 'in', 'on', 'at' in English is used to express a more specific. 'In' is used to express a place in the form of an area or volume, 'on' is used to declare a place on a surface and ‘at' is used to declare a place at a certain point. Contrastive analysis of ‘di’ in Bahasa and ‘in’, ‘on’, ‘at’ in English can be used as an alternative solution for teachers to help students overcome the difficulties encountered in learning English as second language.
Keywords: contrastive analysis ‘di’, particle case ‘in’, ‘on’, ‘at’